Chronic Mucocutaneous Candidiasis in Autoimmune Polyendocrine Syndrome Type 1 - Humbert, Linda; Cornu, Marjorie; Proust-Lemoine, Emmanuelle; Bayry, Jagadeesh; Wemeau, Jean-Louis; Vantyghem, Marie-Christine; Sendid, Boualem (Frontiers in Immunology, 2018)
Autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) is an autosomal recessive disease caused by mutations in the autoimmune regulator (AIRE) gene, characterized by the clinical triad of chronic mucocutaneous candidiasis (CMC), hypoparathyroidism, and adrenal insufficiency. CMC can be complicated by systemic candidiasis or oral squamous cell carcinoma (SCC), and may lead to death. The role of chronic Candida infection in the etiopathogenesis of oral SCC is unclear. Long-term use of fluconazole has led to the emergence of Candida albicans strains with decreased susceptibility to azoles. CMC is associated with an impaired Th17 cell response; however, it remains unclear whether decreased serum IL-17 and IL-22 levels are related to a defect in cytokine production or to neutralizing autoantibodies resulting from mutations in the AIRE gene.